2003
DOI: 10.1074/jbc.m305926200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of S-ovalbumin as a Non-loop-inserted Thermostabilized Serpin Form

Abstract: Ovalbumin, a non-inhibitory member of serine proteinase inhibitors (serpin), is transformed into a heatstabilized form, S-ovalbumin, under elevated pH conditions. The structural mechanism for the S-ovalbumin formation has long been a puzzling question in food science and serpin structural biology. On the basis of the commonly observed serpin thermostabilization by insertion of the reactive center loop into the proximal ␤-sheet, the most widely accepted hypothetical model has included partial loop insertion. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 47 publications
5
65
2
1
Order By: Relevance
“…During embryogenesis, ovalbumin changes to a more heat-stable conformation, while migrating from egg white to amniotic fluid, embryonic organs, and yolk (28). Whether this conformational change of ovalbumin is related (29) or unrelated (30) to classical serpin rearrangement is disputed. Relative to ovalbumin, the paralogues gene Y and gene X have hinge regions that deviate less from the consensus, and these genes, particularly gene Y, may encode inhibitory serpins.…”
Section: Resultsmentioning
confidence: 99%
“…During embryogenesis, ovalbumin changes to a more heat-stable conformation, while migrating from egg white to amniotic fluid, embryonic organs, and yolk (28). Whether this conformational change of ovalbumin is related (29) or unrelated (30) to classical serpin rearrangement is disputed. Relative to ovalbumin, the paralogues gene Y and gene X have hinge regions that deviate less from the consensus, and these genes, particularly gene Y, may encode inhibitory serpins.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning OVA, S-OVA, the thermal stabilizing form of OVA, is produced during the storage of eggs. Yamasaki et al reported that Ser-164, Ser-236, Ser-320 were changed to the D-form in the S-OVA [14]. The estimated %D is 7.9%.…”
Section: Determination Of D-amino Acid Residues In Ovalbuminmentioning
confidence: 99%
“…Because Asp residues can be easily transformed into succinimidyl intermediates, the chiral inversion from L-Asp to D-Asp frequently occurs, therefore, D-Asp residues are often observed in disease/aged proteins [6]. However, some other D-amino acid residues, such as D-Ser and D-Asn, were also formed in a few protein samples [13][14][15]. These reports suggest that various D-amino acid residues are likely to occur without the formation of succinimidyl intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…For the serine residue, rate constant for inversion between l-and d-configuration was reported to be almost the highest among the other residues except cysteine [14]. In the case of S-ovalbumin, only three serine residues in 385-residues polypeptide are determined to be in d-configuration by X-ray crystallographic analysis [10]. In the present study, the effect of point mutation at the conceivable d-serine residues (S164, S236, and S320) was investigated to estimate their contributions to thermostability of S-ovalbumin.…”
mentioning
confidence: 96%
“…During the last decade, some observations were additionally reported [6 -12], but still conclusive explanation has not been achieved so far. Among them, our X-ray crystallographic study [10] did offer some possibilities from unique stand points. S-…”
mentioning
confidence: 98%